Analysis of the Copyright Infringement Lawsuit Against Rachmawati Soekarno in Decision Number 305 K/PDT. SUS-HKI/2014 - Wijaya, Niko; Lie, Gunardi; Putra, Moody Rizqy Syailendra (CV. Rayyan Dwi Bharata, 2024)
Basically, the meaning of the film itself can be said to be a mass communication medium where the content can be related to vital ideas which of course are aimed at the audience and also carry a message. This is the meaning of the film as a work of cultural art being displayed. Therefore, it can be said that the film itself has several functions as a driver of creative work, an educational function and also an informational function. It can be said that because the function of this film is diverse, the function of the film is not only limited to entertainment. The holder of the economic rights or moral rights of the disputed Soekarno film script is Rahmawati but apparently her name was not included so that Rahmawati filed a lawsuit at the court in Central Jakarta against PT Multivisionfus and director Hanung Bramantyo that the basis of the lawsuit was copyright infringement of the copyright in Soekarno, created and directed by Hanung Bramantyo. In the first instance, the lawsuit filed by Rahmawati was explained in the decision of the Central Jakarta District Court that the lawsuit was granted and considered that there were indications of copyright infringement by not including Rahmawati's name and Soekarno's film script, which was committed by Multivision Plus. However, because the defendant did not agree with the decision given by the Central Jakarta court, a cassation was submitted to the supreme court and in the end the appeal was accepted by the supreme court and stated that the figure Soekarno was not someone's creation, but was a real figure who actually lived. and finally died.